2014
DOI: 10.1016/j.marenvres.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Artificial structures in sediment-dominated estuaries and their possible influences on the ecosystem

Abstract: a b s t r a c tArtificial substrates are omnipresent today in most estuaries mostly in form of massive rip-rap used for groynes and jetties. In the Weser estuary, Germany, 60% of the shoreline is covered with such artificial substrates while, natural rocky substrate is lacking, as in all Wadden Sea estuaries. This large quantity of artificial substrates may be colonized by a benthic hard-substrate community which differs from the local natural soft-substrate assemblage. In this study we examined species compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 105 publications
0
11
0
5
Order By: Relevance
“…A recent study also found that H. capensis were more likely to move towards or remain on a Reno mattress structure compared to Z. capensis (Claassens et al ., ), which suggests that this habitat type has some positive feature (food, holdfasts, protection) preferred by H. capensis . Artificial structures have the potential to provide much needed habitat to threatened aquatic species (Guerra‐Garcia et al ., ; Perkol‐Finkel et al ., ; Wetzel et al ., ), but this does not necessarily equate to an overall benefit for the system (or even the species in question), particularly if these artificial habitats displace natural aquatic habitats (Waltham & Connolly, ; Wetzel et al ., ). The Reno mattresses in Thesen Islands Marina did not displace any natural aquatic habitat and thus provide a net increase in habitable environments for H. capensis in the Knysna Estuary.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also found that H. capensis were more likely to move towards or remain on a Reno mattress structure compared to Z. capensis (Claassens et al ., ), which suggests that this habitat type has some positive feature (food, holdfasts, protection) preferred by H. capensis . Artificial structures have the potential to provide much needed habitat to threatened aquatic species (Guerra‐Garcia et al ., ; Perkol‐Finkel et al ., ; Wetzel et al ., ), but this does not necessarily equate to an overall benefit for the system (or even the species in question), particularly if these artificial habitats displace natural aquatic habitats (Waltham & Connolly, ; Wetzel et al ., ). The Reno mattresses in Thesen Islands Marina did not displace any natural aquatic habitat and thus provide a net increase in habitable environments for H. capensis in the Knysna Estuary.…”
Section: Discussionmentioning
confidence: 99%
“…In the Oder, we found filter feeder-predators to be the most numerous at the currents sites, while shredder-predators were the most numerous at the control sites and in the groyne fields. The presence of numerous filter feeders may be beneficial as regards improving water quality in a river such as the Oder: this was noted by Wetzel et al (2014), who studied estuarine ecosystems with groynes in Germany. Among all riverine habitats, the trophic structure of the groyne fields was the most diversified and similar to the structure of the oxbows.…”
Section: Functional Groups Of Caddisflies In the Context Of The Groynmentioning
confidence: 97%
“…Em consequência da importância ecológica da comunidade bentônica, diversas linhas de pesquisas se desenvolvem desde a década de 1970 (Fernandes et al, 2010). Dentre os estudos realizados, destacam-se aqueles que descrevem a dinâmica espaço-temporal no processo de colonização e a estrutura da comunidade em ambientes naturais e artificiais (Carvalho & Uieda, 2004, Nery et al, 2008, Souza et al, 2008, Fernandes et al, 2010, Pereira et al, 2010, Braga et al, 2013, Guerra-Castro & Cruz-Motta, 2014, Wetzel et al, 2014, Bernardino et al, 2015, Oliveira & Manso, 2016, Chagas et al, 2018.…”
Section: Introductionunclassified